A MODEL FOR AGRI-TOURISM OF THE MODEL COMMUNITY IN BAN HUA KHUA, KAE DAM DISTRICT, MAHASARAKHAM PROVINCE - Khampuanbutra, Wanna; Phakprapai, Charin (Journal of Social Science and Cultural, 2024)
The research aims to study 1) the tourism resource base of the Ban Hua Khua model community 2) agri - tourism activities and 3) service provision in agri - tourism destinations. It is a qualitative and quantitative research by survey method, and the population is a purposive sample. The sampling and tools used were: 1) a structured interview form used with village headmen; 7 occupational group leaders and community development specialist. 2) small group discussions with 14 village headmen and occupational group leaders 3 times. 3) closed-ended questionnaires with 114 tourists. Data were analyzed by descriptive statistics, including: percentage, mean, standard deviation integrated with interviews and small group meetings. The results of the study showed that 1) tourism resource base has 5 aspects: 1) Nong Kae Dam is an important water resource for organic vegetables farmimg 2) Heet Sib Song, traditional activity, has been passed down from the past 3) reed and bamboo are used as raw materials for handicraft 4) occupational groups established base on local wisdom, reed mats, basketry and woven cloth. 5) Saphan Mai Kae Dam is an important tourist destination 2) Regarding agri - tourism activities, there are 4 activities: 1) visiting, making, buying the reed mats and basketry of occupational groups. 2) talking and exchange business knowledge with the homestay group 3) visiting and practicing in the farm with mixed vegetable growing group 4) visiting and making souvenirs with the occupational group 3) providing services in agri - tourism site has 5 factors: 1) the community is willing to provide services and care 2) the community is true natural environment tourist attraction 3) the community has their own agricultural knowledge 4) the community has expertise in service management 5) the community is a place where tourists can access conveniently by various types of vehicles.